Sri Lanka Development Update, November 2017 : Creating Opportunities and Managing Risks for Sustained Growth - World Bank (Washington, DC, 2017)
Despite significant challenges, Sri Lanka's economic performance remained broadly satisfactory in the first half of 2017. The corrective policy measures taken in the monetary and fiscal fronts have led to gradual stabilization. The construction sector's rapid recovery supported by a strong rebound in investment was partially able to mitigate the impact of inclement weather conditions on the real sector. External buffers strengthened thanks to foreign exchange purchases and improved capital flows. Inflation has risen since the second half of 2016 on account of drought and changes to the VAT Act. Authorities pursued the economic reform agenda presented in the government policy statements, albeit at a slower pace, owing to the difficulties faced in a complex political environment and institutional constraints on policy implementation. Parliament passed a new Inland Revenue Law in September 2017, which marks a key milestone towards sustainable revenue-led fiscal consolidation.